Entamoeba histolytica: Observations on metabolism based on the genome sequence - Anderson, Iain J.; Loftus, Brendan J. (Experimental parasitology, 2005)
The sequencing of the genome of Entamoeba histolytica has allowed a reconstruction of its metabolic pathways, many of which are unusual for a eukaryote. Based on the genome sequence, it appears that amino acids may play a larger role than previously thought in energy metabolism, with roles in both ATP synthesis and NAD regeneration. Arginine decarboxylase may be involved in survival of E. histolytica during its passage through the stomach. The usual pyrimidine synthesis pathway is absent, but a partial pyrimidine degradation pathway could be part of a novel pyrimidine synthesis pathway. Ribonucleotide reductase was not found in the E. histolytica genome, but it was found in the close relatives Entamoeba invadens and Entamoeba moshkovskii, suggesting a recent loss from E. histolytica. The usual eukaryotic glucose transporters are not present, but members of a prokaryotic monosaccharide transporter family are present.